(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
In public areas, QR codes are being utilized more and more for information sharing, marketing, and payment. But because of their ease of use and user confidence, they are open to abuse, such as phishing, malware distribution, and illegal data access. In order to examine the effects and create defenses, this study replicates actual QR code-based attack scenarios in controlled ethical hacking environments. In order to propose defenses strategies like QR code validation, user awareness, and embedded link scanning, the paper investigates how to set up safe lab conditions for QR-based social engineering, redirection attacks, and malicious payload.